1990
DOI: 10.1149/1.2086708
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Nature of Silicon Nitride‐Indium Phosphide Interface and Rapid Thermal Annealing for InP MISFETs

Abstract: Rapid thermal annealing (RTA) of the ion implanted indium phosphide (InP) compound semiconductors in pure nitrogen or hydrogen was investigated for the fabrication of metal-insulator-semiconductor field-effect transistors (MISFETs). InP was encapsulated during RTA by 500A silicon nitride films made using PECVD at 300~ and 500 mtorr with a 13.56 MHz RF power density of 50 mW/cm 2. A sequence of high-resolution x-ray photoelectron spectra were obtained at four depths through the silicon nitride-InP interfacial r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The 30 min CF4 plasma cleaning was necessary to remove the film deposits on the chamber walls from previous deposition runs. Our previous experiments (17,18) have indicated that 30 min were long enough for the removal of the films from prior runs. Then the substrates were loaded into the chamber immediately after the initial clean to minimize any native oxide growth.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 30 min CF4 plasma cleaning was necessary to remove the film deposits on the chamber walls from previous deposition runs. Our previous experiments (17,18) have indicated that 30 min were long enough for the removal of the films from prior runs. Then the substrates were loaded into the chamber immediately after the initial clean to minimize any native oxide growth.…”
Section: Methodsmentioning
confidence: 99%
“…An argon ion beam was used for surface cleaning which was operated at 2 keV. The details of the XPS technique as applied to insulator/InP interfaces have recently been reported (17,18).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consider the oxidation of gate d~ is also expressed in general as d~ = d(LhNpol:0 [19] Combining Eq. [18] and [19] and assuming dh = dL, Npoly is solved as Npol, = No ho \Ifo/ [20] where Lo is the initial gate length. Thus, the two-dimensional effect is expressed by the factor…”
Section: Two-dimensional Effectmentioning
confidence: 99%